Single‐Pixel Infrared Miniaturized Spectrometer Enabled by Ultra‐Broadband Reconfigurable Photodetection - Wenyue Liang; Xianghong Nan; Wenfeng Cai; Ning Tan; Qilin Zheng; Yuyao Lu; Yongyue Huang; Jiahao Yan; Dangyuan Lei; Long Wen; Yanjun Liu; Qin Chen (Advanced Science)
Abstract Miniaturized spectrometers utilizing a single reconfigurable photodetector (PD) are highly attractive in the infrared (IR) range due to their advantages in terms of cost, ease of integration, and reduced system complexity. However, such devices usually suffer from either limited wavelength tuning range or high spectral correlation in spectral sampling. Here, a new concept based on tunable guided mode resonances and surface plasmon resonances in a simple liquid crystal/Au stack is proposed to break the wavelength tuning range limit and simultaneously enable low spectral correlation. A chip‐scale IR spectrometer using a single‐pixel PbS PD is realized with a remarkably large wavelength tuning range over 850 nm (1150–2000 nm) and high fidelity (mean square error ≈0.001) in spectrum measurement. Such a novel technique is applied in plastic sorting and demonstrated remarkable improvement in sorting accuracy benefiting from its broadband property and distinct spectral responses at various sampling biases. Furthermore, a post‐tuned operating mode for efficient and accurate spectroscopy is demonstrated by customizing the wavelength/bias scanning strategies, demonstrating the high flexibility of this technology. Full‐vector analysis considering the interface anchoring effect and the anisotropic gradient refractive index distribution of liquid crystal is conducted to reveal the fundamental principles of broadband light modulation.